1982
DOI: 10.1111/j.1365-2672.1982.tb04683.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sublethal injury by heating, freezing, drying and gamma‐radiation on the duration of the lag phase of Salmonella typhimurium

Abstract: The duration of the lag phase of Salmonella typhimurium surviving heat, freezing, drying and gamma‐radiation was used to indicate the time needed to repair sublethal injury. Following equivalent lethal treatments, heat and freeze‐injured cells needed longer to repair than those injured by drying or gamma‐radiation. Measurement of repair on membrane filters showed that in a heat‐injured population having a lag time of 9 h, some individual cells needed up to 14 h to recover maximum tolerance to 3% NaCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 27 publications
(15 reference statements)
4
66
1
Order By: Relevance
“…However, when the stress was not lethal, the cells could adapt and subsequently grow in the new condition. Other similar studies (14,18) have also reported that in sublethally stressful environments, cell populations suffer an initial loss and then may recover.…”
Section: Discussionmentioning
confidence: 87%
“…However, when the stress was not lethal, the cells could adapt and subsequently grow in the new condition. Other similar studies (14,18) have also reported that in sublethally stressful environments, cell populations suffer an initial loss and then may recover.…”
Section: Discussionmentioning
confidence: 87%
“…The proportion of sublethally damaged cells is determined by the difference on counts between cells recovered in a non-selective media and a selective media after the treatment. The selective media more commonly used to detect the membrane damage is agar with sodium chloride added (Mackey & Derrick, 1982). Fig.…”
Section: Membrane Damage Of Salmonella Typhimurium and S Aureus Cellmentioning
confidence: 99%
“…4), discrepancies between predicted growth regions and observed growth curves were found for initial bacterial concentrations of 10 2 and 10 0 CFU ⅐ ml Ϫ1 . The change from an inoculum of approximately 10 2 CFU ⅐ ml Ϫ1 maintained at 30°C for 14 h to an inoculum of about 1 CFU ⅐ ml Ϫ1 starved for 840 h at 30°C led to an increase in lag time from 32.6 to 66.6 h. The extension of lag phase with physical injury of cells has been frequently reported (14,17,21,22), and models describing the effect of heat injury on subsequent lag period have been published for L. monocytogenes (6,7,23). Albertson et al…”
mentioning
confidence: 98%